Pengaruh Literasi Wakaf dan Theory of Reasoned Action Terhadap Intensi Berwakaf Menggunakan Berkahwakaf.Id (Studi Pada Generasi Z dan Milenial di Kota Serang) - Muhamad Sihabudin; Moh. Mukhsin; Najmudin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The use of digital technology to collect waqf funds responded to the widespread use of digital technology in daily life. Generation Z and millennials, familiar with digital technology, are targeted for online waqf collection. However, the berkahwakaf.id platform is considered insufficient in fostering waqf intentions among these generations. One theory explaining the determinants of intention is the Theory of Reasoned Action (TRA). This research aims to determine the effect of waqf literacy and TRA on waqf intentions using berkahwakaf.id. The independent variable TRA includes attitudes and subjective norms, adding waqf literacy as an additional variable. This research is associative quantitative with a non-probability sampling technique, purposive sampling. The population consists of Generation Z and millennials in Serang City, with a sample size of 100 respondents obtained through a Likert scale questionnaire. The findings show that waqf literacy has a positive but not significant influence on waqf intentions, meaning changes in waqf literacy do not significantly affect waqf intentions. Attitude has a positive and significant influence on waqf intentions. So, a more positive attitude towards waqf using money increases the intention to donate. Subjective norms also significantly influence waqf intentions. The greater the external influence, the higher the waqf intention. Simultaneously, all independent variables have a positive and significant impact on waqf intentions via berkahwakaf.id, with an influence size of 51.6%, while the remaining 48.4% is influenced by unobserved variables.